Exploring the pubertal challenges of female adolescents with blindness - zilehuma; Naeema Sarfraz (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the unique pubertal challenges and the experiences faced by female adolescents with blindness. Method: The qualitative study was conducted from October 2023 to August 2024 at the Department of Psychology, University of Central Punjab, Lahore, Pakistan, and comprised female adolescents with blindness aged 16-19 years. Data was collected using a semi-structured interview protocol. Data was subjected to interpretative phenomenological analysis through which emergent and subordinate themes were generated. Results: Of the 8 females with age ranging 17-19 years, 7(87.5%) lived in a nuclear family system, while 1(12.5%) lived in a joint family system. Superordinate themes included pubertal knowledge and body transformation, spontaneous metamorphosis, challenges in menstrual management, puberty-related health concerns, self-reliance and independence, and spiritual journey and navigating challenges. Conclusion: A need was noted for tailored support systems and accessible resources to better assist female adolescents with blindness during puberty in Pakistan. Key Words: Pubertal challenges, Blindness, Lived experiences.